Influence of bio-derived agar addition on the electrochemical performance of LiFePO4 cathode powders for Li-ion batteries. Issue 9 (15th June 2019) - Lu, Chung-Hsin; Li, Wen Yuan; Subburaj, T.; Ou, Chang Ying; Kumar, P. Senthil
Abstract: Olivine structured LiFePO4 cathode materials were successfully synthesized via a newly developed eco-friendly sol-gel process. In this study, bio-derived natural agar powders were used as chelating agents as well as carbon sources for the first time. The impacts of different agar concentrations (3 wt%–12 wt%) and calcination temperatures (400 °C–700 °C) on the structural and electrochemical properties of LiFePO4 /C powder were investigated in detail. XRD analysis showed that as the concentration of agar reached 6 wt%, a LiFePO4 phase was obtained in N2 atmosphere with 700 °C heating for 8 h. Moreover, increasing the agar concentration to 12 wt% significantly lowered the calcination temperature to 500 °C for the formation of LiFePO4 phase. Particle size distribution spectra also revealed that addition of up to 12 wt% agar concentration reduced the particle sizes of the as-prepared LiFePO4 powder. LiFePO4 powder synthesized with 12 wt% agar concentration at 600 °C exhibited an initial specific discharge capacity of 147 mA h/g at C/10 rate and maintained 146 mA h/g at the end of 50 th cycle in 2–4.2 V window, indicating excellent capacity retention. The analysis of electrochemical impedance spectra and CV test indicated that the charge transfer resistance and potential difference were effectively reduced.